2020
DOI: 10.5455/aim.2020.28.4-11
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Preclinical and Clinical Studies Published in Medical Journals of Bosnia and Herzegovina: Methodology Issues

Abstract: Introduction: Results of preclinical and clinical studies in medicine could be trusted only if their design and statistical analysis were appropriate. Aim: The aim of our study was to investigate whether preclinical and clinical studies published in medical journals of Bosnia and Herzegovina satisfy basic requirements for appropriate design and statistical interpretation of data. Methods: Preclinical and clinical studies published in medical journals of Bosnia and Herzegovina were retrieved from the PubMed dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 104 publications
0
5
0
Order By: Relevance
“…Number and percent of the evaluated studies that failed to meet each of the methodological criteria tested, the number of the evaluated criteria not satisfied per country, and the number of studies that satisfied more than 4 criteria per country is presented in Table 2 . References of the analyzed studies from Bosnia and Herzegovina could be found in our previous publication ( 12 ), while the references of the studies analyzed from Croatian ( 17 - 59 ), Slovenian ( 60 - 92 ) and Serbian medical journals ( 93 - 135 ) are given on the list at the end of this article.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Number and percent of the evaluated studies that failed to meet each of the methodological criteria tested, the number of the evaluated criteria not satisfied per country, and the number of studies that satisfied more than 4 criteria per country is presented in Table 2 . References of the analyzed studies from Bosnia and Herzegovina could be found in our previous publication ( 12 ), while the references of the studies analyzed from Croatian ( 17 - 59 ), Slovenian ( 60 - 92 ) and Serbian medical journals ( 93 - 135 ) are given on the list at the end of this article.…”
Section: Resultsmentioning
confidence: 99%
“…The following search strategy was used for each country separately to implement inclusion and exclusion criteria and select the pool of clinical/observational studies for further analysis: (“Title of the journal 1” [All Fields] OR „title of the journal 2“ [All Fields] OR ...) AND ((“observational study”[Publication Type] OR “observational studies as the topic”[MeSH Terms] OR “observational study”[All Fields]) OR (“clinical trial”[Publication Type] OR “clinical trials as the topic”[MeSH Terms] OR “clinical trial”[All Fields])) Filters: Free full text. The data for Bosnia and Herzegovina was used from our previous study published earlier this year ( 12 ). The size of the study sample for clinical/observational studies (n=43) was calculated based on the following assumptions: rate of inappropriate research design 0.5 ( 13 ) and width of the 95% confidence interval ± 0.15.…”
Section: Methodsmentioning
confidence: 99%
“…Regardless of how the new indicators will be constructed, attributing to a co-author only a fraction of citations of his/her paper would (e.g., by dividing number of citations of a paper with number of the co-authors) surely decrease inflation of co-authorship in modern biomedical scientific literature. The accuracy of citation of a certain article is the key to perform a proper scientometric analysis, and editors of the magazine have to take into account very strict rules when quoting references ( 23 - 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…The average impact factor of the studies was about one, and the average publication date was less than 5 years. [6] Scientometric study analyses India's medical activities during the period 1999-2008, publication growth rate, quality of papers, India's ranking in the global context, International collaboration and Indian collaboration are studied. This study evaluates the research results for different types of Indian medical colleges, hospitals, research institutes, universities and research foundations and the characteristics of literature published in Indian and foreign journals.…”
Section: Related Literaturementioning
confidence: 99%